2018
DOI: 10.3748/wjg.v24.i45.5120
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor regulates expression of microRNA-22 and downstream signaling pathway in apoptosis of pancreatic acinar cells

Abstract: AIMTo elucidate the underlying mechanism that microRNA-22 (miR-22) promotes the apoptosis of rat pancreatic acinar cells (AR42J) and the elements that regulate the expression of miR-22.METHODSOne hundred nanomoles per liter of caerulein (Cae) was administrated to induce the apoptosis of AR42J cells and the apoptosis rate was detected by flow cytometry analysis. An amylase assay kit was used to measure the amylase expression level in the supernatant. Quantitative real-time PCR (qRT-PCR) was adopted to measure m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…While we cannot find any relevant data regarding miR-6132 and tumors, the expression of miR-22 and miR-4539 in cancer tissue has been studied in gastric cancer, rhabdomyosarcoma, breast cancer, prostate cancer, osteosarcoma and papillary thyroid cancer (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Most studies have reported that, in contrast to their expression levels in the blood, the expression levels of these miRNAs are decreased in cancer tissue.…”
Section: Discussionmentioning
confidence: 98%
“…While we cannot find any relevant data regarding miR-6132 and tumors, the expression of miR-22 and miR-4539 in cancer tissue has been studied in gastric cancer, rhabdomyosarcoma, breast cancer, prostate cancer, osteosarcoma and papillary thyroid cancer (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Most studies have reported that, in contrast to their expression levels in the blood, the expression levels of these miRNAs are decreased in cancer tissue.…”
Section: Discussionmentioning
confidence: 98%
“…This is the case for miR-124-3p, where differential splicing produces the GRb isoform, no longer harboring its binding site, which in turn acts as a negative inhibitor of GRα (90,162). Tying this to recent studies, demonstrating that the GR can itself influence miRNA expression profiles (125)(126)(127), the intricacies of miRNA-GR regulation and response to GCs are becoming exponentially complex.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, miR-22 expression was shown to be elevated in AR42J cells following the induction of apoptosis. A GR binding site was identified in the promoter region of miR-22, while GR was shown to be able to repress miR-22 expression (125). In addition, a recent profiling study in triple-negative breast cancer suggested the ability of GR to influence multiple miRNA expression profiles (126), while in the study by Tejos-Bravo et al (127), neuron-specific GR knockout mice exhibited altered miRNA expression profiles in a sex-dependent manner.…”
Section: Mirnas In Glucocorticoid Signalingmentioning
confidence: 99%
“…Genes involved in the neuroactive ligand-receptor interaction signaling pathway and apoptosis signaling pathway are likely related to the pathological mechanism of depression; therefore, genes in these pathways are key targets for the treatment of depression. Additionally, the connection between these pathways in depression may be a focus in the study of depression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NR3C1 , which encodes GR, is related to affective disorders , and any abnormalities in NR3C1 affect the function and activity of GR, thereby leading to disorders of the neuroendocrine system [ 27 ]. Moreover, NR3C1 downregulation promotes the expression of micro-RNA-22, which results in the increased expression of downstream genes, namely, Bcl-2-associated agonist of cell death, Bax , and caspase-3 , and decreased expression of Bcl-2 and Bcl-xL , thereby promoting cell apoptosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%